Equilibrium Job Turnover and the Business Cycle - Carlos Carrillo-Tudela; Alex Clymo; Melvyn Coles (Institute of Labor Economics (IZA), 2021)
This paper develops and estimates a fully microfounded equilibrium business cycle model of the US labor market with aggregate productivity shocks. Those microfoundations are consistent with evidence regarding the underlying distribution of firm growth rates across firms [by age and size] and, when aggregated, are consistent with macro-evidence regarding gross job creation and job destruction flows over the cycle. By additionally incorporating on-the-job search, we systematically characterise the stochastic relationships between aggregate job creation and job destruction flows across firms, gross hire and quit flows [churning] by workers across firms, as well as the persistence and volatility of unemployment and worker job finding rates over the cycle.
Keywords: E24; E32; J62; J63; 330; business cycle; firm dynamics; job search